Restaurant Readiness in the implementation of Health Protocols during Covid-19 Pandemic in Simalungun Regency - Ritonga, Abdul Kadir (Technium Social Sciences Journal, 2021)
This pandemic has had a major impact on all sectors including the economy. Currently, many countries are preparing for a new normal in the midst of the Covid-19 pandemic, including Indonesia. Restaurant is one of the public places and hospitality service that must be prepared for the New normal. The purpose of this study was to determine the readiness of restaurants in Simalungun Regency, North Sumatera during the new normal period. The research design used observation and quantitative research. The number of samples was 40 restaurant visitors in Simalungun Regency which were selected by proportional random sampling. Data collection techniques through direct observation. Data analysis was carried out descriptively to determine the readiness of restaurants during the new normal period. The results showed that most restaurants in Simalungun Regency had implemented health protocols. Health promotion for behavior change is needed continuously through health campaigns and strict supervision of the implementation of health protocols in restaurants to suppress the transmission of Covid-19. It can be concluded that restaurants in Simalungun Regency are ready to implement health protocols in the New Normal Era in the face of covid 19.